Building Participation in Sustainable Mice Event Based on Social Identity in Medan City - Nursiah Fitri; Harris Pinagaran Nasution; Desri Wiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The city of Medan has been designated by the government as a MICE destination in Indonesia. MICE events (Meetings, Incentives, Conventions and Exhibitions/Events) are important activities in the development of the tourism industry. MICE activities use many facilities in the tourism industry, such as transportation, accommodation, various attractions and entertainment including souvenirs. Organizing a MICE event in a destination has a multiplier effect not only in the economic field but also in the social and environmental fields. Therefore Sustainable MICE events have become a global trend that aims to maintain the sustainability of quality economic, social and environmental life. The implementation of Sustainable MICE events will provide a positive value for a destination to be selected by a world association as a preferred destination. Several studies have been conducted to obtain mechanisms underlying a sustainable MICE industry. This study aims to examine 1) the effect of social identity in the implementation of sustainable MICE events, 2) the effect of social identity on the desire to participate, 3) the effect of the implementation of sustainable MICE events on the desire to participate and 4) the effect of social identity through the implementation of sustainable MICE events on the desire to participate. The population and samples were taken from the community in the IVENDO association which is an association of MICE event organizers, 94 participants who had been event organizers in the city of Medan. The sampling technique uses a non-probability sample using a saturated sample. Data collection was carried out using a questionnaire. Data analysis technique uses PLS Smart 3.0. The results of the study show that social identity variables have a positive and significant effect on sustainable MICE events. The social identity variable has a positive and significant effect on the desire to participate. The implementation variable of sustainable MICE events influences the desire to participate. Social identity variables through sustainable MICE events have a positive and significant effect on the desire to excel.